2016
DOI: 10.1007/s13224-015-0827-1
|View full text |Cite
|
Sign up to set email alerts
|

Second Trimester Medical Termination of Pregnancy with Combined Intracervical and Intravaginal Misoprostol: Comparative Analysis with Intravaginal Misoprostol—A Pilot Study

Abstract: Context Intravaginal placement of misoprostol has been used extensively to terminate second trimester pregnancies. Intracervical misoprostol is an alternative method of termination of pregnancy for women in this period of gestation. Objective To assess the efficacy and safety of combined intracervical and intravaginal misoprostol in the management of mid-trimester medical termination of pregnancy and to compare it with intravaginal misoprostol. Materials and MethodsIn this IRB approved prospective study, twent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 9 publications
0
7
1
Order By: Relevance
“…Two studies included women who underwent induced fetal demise immediately before abortion [ 17 , 18 ]. Nine studies included a total of 172 women with a scarred uterus [ 16 , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] ]. In three studies, women with a scarred uterus comprised 22% of the population [ 18 , 21 , 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two studies included women who underwent induced fetal demise immediately before abortion [ 17 , 18 ]. Nine studies included a total of 172 women with a scarred uterus [ 16 , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] ]. In three studies, women with a scarred uterus comprised 22% of the population [ 18 , 21 , 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…Four trials with 347 total subjects compared oral to vaginal routes of misoprostol ( Fig. 9 , Supplements 12A and 13A) [ 19 , 22 , 50 , 51 ]. The oral group had higher ongoing pregnancy rates at 24 h (RR 3.60, 95% CI 1.99–6.51, moderate certainty evidence) and 48 h (RR 8.01, 95% CI 1.74–36.87, low certainty evidence).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Availability of the health care centre in urban areas may help the women to decide in earlier and correct stage to terminate the pregnancy; but the rural women is mostly in dilemma and post termination care is found substantial [6,28,29,30] . The major factors that are influencing and disturbing the termination process for the individual are age, age at sexual activity onset, emotional/ sentimental, educational background, income issues, religion, occupation, fear about abortion procedure, availability of appropriate health care, cooperation of the family, location of abortion, types of treatment, post abortion care and other ethical and legal issues [14,31,32] . Many studies suggested that the parity is a major factor that influencing the success of medical termination of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Also, it was found for better local drug action. Thus the overall dosage of the drug and its side effects is reduced [14] . For STT, the dual-therapeutic effect of mifepristone and misoprostol seems to have the highest and the shortest time interval of termination.…”
Section: Introductionmentioning
confidence: 99%